3D Printing of Metals - Gupta, Manoj (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
3D printing is rapidly emerging as a key manufacturing technique that is capable of serving a wide spectrum of applications, ranging from engineering to biomedical sectors. Its ability to form both simple and intricate shapes through computer-controlled graphics enables it to create a niche in the manufacturing sector. Key challenges remain, and a great deal of research is required to develop 3D printing technology for all classes of materials including polymers, metals, ceramics, and composites. In view of the growing importance of 3D manufacturing worldwide, this Special Issue aims to seek original articles to further assist in the development of this promising technology from both scientific and technological perspectives. Targeted reviews, including mini-reviews, are also welcome, as they play a crucial role in educating students and young researchers.